2019
DOI: 10.12998/wjcc.v7.i1.49
|View full text |Cite
|
Sign up to set email alerts
|

Value of contrast-enhanced ultrasound combined with elastography in evaluating cervical lymph node metastasis in papillary thyroid carcinoma

Abstract: BACKGROUNDCervical lymph node metastasis in papillary thyroid carcinoma (PTC) affects the treatment and prognosis of patients. Ultrasound is a common imaging method for detecting cervical lymph nodes in PTC patients; however, it is not accurate in determining lymph node metastasis.AIMTo evaluate the value of contrast-enhanced ultrasound combined with elastography in evaluating cervical lymph node metastasis in PTC.METHODSA total of 94 patients with PTC were recruited. According to pathological results, lymph n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…On the other hand, very aggressive PTMC might be sometimes observed [3]. One of the most unfavorable clinicopathological features of aggressive PTMCs is lymph node metastasis [7, 8]. Jiang et al suggested that the presence of central or lateral lymph node metastases in papillary thyroid cancer (PTC) cases affects the prognosis and treatment of the individuals [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, very aggressive PTMC might be sometimes observed [3]. One of the most unfavorable clinicopathological features of aggressive PTMCs is lymph node metastasis [7, 8]. Jiang et al suggested that the presence of central or lateral lymph node metastases in papillary thyroid cancer (PTC) cases affects the prognosis and treatment of the individuals [8].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most unfavorable clinicopathological features of aggressive PTMCs is lymph node metastasis [7, 8]. Jiang et al suggested that the presence of central or lateral lymph node metastases in papillary thyroid cancer (PTC) cases affects the prognosis and treatment of the individuals [8]. Moreover, these metastases increase the rate of regional recurrence and mortality, especially in elderly patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, preoperatively identified macroscopic metastatic LNs have prognostic significance and are regarded as clinically apparent metastatic LNs, whereas most micrometastatic nodes that are undetected by imaging have little clinical significance [ 134 ]. Recent studies have investigated the roles of advanced US imaging modalities, such as US elastography [ 149 150 151 152 153 ], contrast-enhanced US [ 154 155 156 157 ], and US microvascular imaging [ 158 ]. However, there are insufficient data on their clinical utility.…”
Section: Diagnosis Of Cervical Metastatic Lymph Nodes On Usmentioning
confidence: 99%
“…PTC develops indolently, but 30% to 80% of patients with PTC demonstrate highly aggressive diseases, such as cervical lymph node metastasis ( 3 ). The presence of cervical lymph node metastasis (CLNM) is well associated with an increased risk of recurrence and affects the postoperative survival rate in select patient populations ( 4 , 5 ). The early diagnosis of lymph node metastasis can guide clinicians to perform aggressive therapeutic neck dissection.…”
Section: Introductionmentioning
confidence: 99%